Stages of Ability to Recognize Number Concepts Through Modified Apron Media for Children with Special Needs: Tahapan Kemampuan Mengenal Konsep Bilangan Melalui Media Apron Modifikasi Pada Anak Berkebutuhan Khusus - Ratna Dwi Kusuma Ning Putri; Mohammad Faizal Amir (Indonesian Journal of Education Methods Development, 2021)
The concept of equality in mathematics is fundamental to be learned by elementary school level students. Knowledge of equations in mathematics is an essential prerequisite for learning algebra at a higher level. Especially in the ability to recognize the concept of numbers in children with special needs which can be developed using arithmetic apron media. This study uses a literature study approach. The subject is an extraordinary elementary school student. The data obtained by researchers came from various literatures that have been reviewed and analyzed by researchers. The results showed that students could reach the stage of introducing the concept of numbers